Roles of Pyruvate, NADH, and Mitochondrial Complex I in Redox Balance and Imbalance in β Cell Function and Dysfunction - Xiaoting Luo; Rongrong Li; Liang-Jun Yan (Journal of Diabetes Research)
Pancreatic β cells not only use glucose as an energy source, but also sense blood glucose levels for insulin secretion. While pyruvate and NADH metabolic pathways are known to be involved in regulating insulin secretion in response to glucose stimulation, the roles of many other components along the metabolic pathways remain poorly understood. Such is the case for mitochondrial complex I (NADH/ubiquinone oxidoreductase). It is known that normal complex I function is absolutely required for episodic insulin secretion after a meal, but the role of complex I in β cells in the diabetic pancreas remains to be investigated. In this paper, we review the roles of pyruvate, NADH, and complex I in insulin secretion and hypothesize that complex I plays a crucial role in the pathogenesis of β cell dysfunction in the diabetic pancreas. This hypothesis is based on the establishment that chronic hyperglycemia overloads complex I with NADH leading to enhanced complex I production of reactive oxygen species. As nearly all metabolic pathways are impaired in diabetes, understanding how complex I in the β cells copes with elevated levels of NADH in the diabetic pancreas may provide potential therapeutic strategies for diabetes.